2015
DOI: 10.1111/jam.12870
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the virucidal efficacy of peracetic acid, potassium monopersulphate and sodium hypochlorite on bacteriophages P001 and MS2

Abstract: This is the first comparative study to investigate through suspension and surface tests the difference in resistance to peroxy compounds between a reference bacteriophage (P001) used to evaluate phagicidal concentrations in European standards and a surrogate of EVs (MS2). Results underline the importance of validation tests on pertinent surrogates of viruses or bacteriophages to adjust the concentration of disinfectants for use in the food and water industries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Morin et al . [29] reported >4 log reduction for MS2 when exposed to 0.1% NaOCl for 15 minutes on stainless steel carriers. In addition to the longer contact time, the fact that they used larger surface carriers (20x10x1mm) and spread the 10-μL “spill” to cover 70% of the surface before drying for 1 hour, enhancing the impact of drying, might explain their increased inactivation compared with our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Morin et al . [29] reported >4 log reduction for MS2 when exposed to 0.1% NaOCl for 15 minutes on stainless steel carriers. In addition to the longer contact time, the fact that they used larger surface carriers (20x10x1mm) and spread the 10-μL “spill” to cover 70% of the surface before drying for 1 hour, enhancing the impact of drying, might explain their increased inactivation compared with our results.…”
Section: Discussionmentioning
confidence: 99%
“…MS2 is commonly used in environmental studies as a model for enteric viruses and is known to be resistant to several disinfection processes [20,29]. As such, MS2 was expected to be a conservative surrogate for the Ebola virus.…”
Section: Methodsmentioning
confidence: 99%
“…Because it is similar to some enteric viruses, the MS2 bacteriophage (an RNA bacteriophage) is the surrogate most commonly proposed and used to assess the efficacy of virucidal decontaminants (D’Souza and Su ; Boudaud et al ). MS2 has been reported to have a sensitivity (D’Souza and Su ; Morin et al ) to selected disinfectants recommended for FMDV decontamination (Krug et al ; Krug et al ). Many methods have been described for detection of MS2 from various inanimate surfaces but few address detections of MS2 from complex environmental matrices (Krug et al ; Krug et al ; Shim et al ).…”
Section: Introductionmentioning
confidence: 99%
“…). Previous study with an Stx phage had shown more than 3 log 10 PFU inactivation after the first minute of chlorination at 10 ppm (Allué‐Guardia et al ., ) as well as after 3 min at 5 ppm (Duran et al ., ), and phages λ and MS2 were inactivated at 2500 ppm after 30 min (Halfhide et al ., ), 5000 ppm after 1 min (D'Souza & Su, ) and 4 ppm after 15 min (Morin et al ., ). In contrast, Muniesa and coworkers found that three coliphages, namely a somatic coliphages and two phage infecting O157:H7, were highly resistant to hypochlorite (10 and 20 ppm) because they observed at most ~1 log 10 PFU reductions after a 30‐min incubation (Muniesa et al ., ).…”
Section: Resultsmentioning
confidence: 97%